Soybean Seeds Produced in Out Season in West of Paraná State – Brazil - Ávila, Marizangela Rizzatti; Braccini, Alessandro de Lucca e; Albrecht, Leandro Paiola; Scapim, Carlos Alberto (IntechOpen, 2011)
None